Phylogenetic position of the poorly known montane cascade frog Amolops monticola (Ranidae) and description of a new closely related species from Northeast India. Issue 21 (3rd June 2021) - Patel, Naitik G.; Garg, Sonali; Das, Abhijit; Stuart, Bryan L.; Biju, S.D.
ABSTRACT: The phylogenetic position of Amolops monticola, a cascade frog species known for over 150 years, remains unknown. Yet over the years new taxa have been frequently described in the ambiguously recognised A. monticola species group, based on morphology and presumed phylogenetic affinities. Here we report fresh collections of A. monticola from the Indian Himalayas and clarify its identity with new molecular and morphological evidence. Furthermore, our surveys in the Northeast Indian State of Arunachal Pradesh have led to the discovery of another new species in the A. monticola group from Siang River basin encompassing the Adi hills (historically known as Abor hills). The new species, formally described as Amolops adicola sp. nov., is morphologically distinguished from its congeners by a suite of characters that include adult size, body colouration and markings, skin texture, snout shape, foot webbing and digit tip morphology, in addition to significant morphometric distinctness observed in principal component analysis. Phylogenetically, the new species is recovered as a well-supported sister taxon of A. monticola, based on Bayesian and maximum likelihood inferences as well as Bayesian Poisson Tree Processes (bPTP) species delimitation analysis using 2001 bp of mitochondrial DNA (16S rRNA, cytochrome c oxidase subunit I and NADH dehydrogenase 2). It differs from other known members of the group by considerable genetic distances in the studied loci: ≥ 4.3% at 16S, ≥ 6.1% at COI and ≥ 7.0% at ND2. The study also shows for the first time the phylogenetic affinities of another Indian member of the A. monticola group, A. kohimaensis . Altogether, the new insights resolve the long-existing enigma surrounding A. monticola and facilitate a better understanding of systematic relationships within the large A. monticola species group. Our findings also emphasise the need for further dedicated studies on the cascade frogs of Northeast India.